Report on a portion of the District of Athabasca [electronic resource] : comprising the country between Peace River and Athabasca River north of Lesser Slave Lake - McConnell, R. G. (Richard George), 1857-1942.; Geological Survey of Canada. ([Ottawa? : s.n.], 1893)
At head of title: Geological Survey of Canada. Alfred R.C. Selwyn. director. "Geological Survey of Canada. Part D. Annual report, vol. v, 1889-90-91." --[p. 4D] Includes biographical references. Electronic reproduction. Mode of access: Internet. 44